Architectural and Landscape Design of Tourist Infrastructure, Alternative New Tourism Routes - Mustafayevna, Rashidova Nafisa; Murodovna, Rakhmatova Mekhriniso (International Journal on Integrated Education, 2023)
This article presents examples of the experience of cities with the most attractive and convenient features of the architectural and landscape design of the tourist infrastructure and the development of alternative new tourist routes for the Fatherland and abroad.